National Consultation-cum-Brain Storming Session on Fortification of Edible Salt with Micronutrients - Kapil, Umesh; Sachdeva, H P (Indian Journal of Community Health, 2018)
Micronutrient malnutrition (MNM) can affect all age groups, but young children and women of reproductive age tend to be among those most at risk of developing micronutrient deficiencies. In India, Iodine Deficiency Disorders and Iron Deficiency Anaemia are important Public Health problems.No state in India is free from iodine deficiency. Out of 343 districts surveyed, 286 are reported have Iodine Deficiency Disorders. Iron Deficiency Anaemia is reported in about 60% population across all age groups. The magnitude of vitamin B12 Deficiency is reported to be about 47% in urban population of Delhi while Zinc Deficiency is reported in about 44% amongst Indian children. In addition, there are other micronutrients and minerals like folic acid which are of public health concern. Fortification of food is one of three primary strategies to combat micronutrient deficiencies. Fortification is defined by the World Health Organization (WHO) and the Food and Agricultural Organization of the United Nations (FAO) as "the practice of deliberately increasing the content of an essential micronutrient, i.e. Vitamins and minerals (including trace elements) in a food irrespective of whether the nutrients were originally present in the food before processing or not, so as to improve the nutritional quality of the food supply and to provide a public health benefit with minimal risk to health”. Food fortification is one of the most cost effective ways to make up for the deficient vitamins and minerals in low quality diets. Edible salt is the most widely used food vehicle for fortification with micronutrients. Fortification of salt with iodine, under the National Iodine Deficiency Disorders (IDD) Control Programme, has been the strategy in operation in the entire country as a universal policy since 1962 to combat IDD. This has led to prevention and control of IDD in the country. In 1970s, an attempt was made to develop Iron fortified salt (IFS) or edible salt fortified with Iron. Efficacy trials and multi-centric effectiveness trials were conducted and documented positive results. However, with the policy focus on Universal Salt Iodization Programme in the country, IFS was not introduced in the country. Subsequently in 1980s, the National Institute of Nutrition (NIN), India, Hyderabad developed edible salt fortified with Iron and Iodine, referred to as double fortified salt (DFS) or NIN-DFS. Efficacy studies were conducted with DFS with mixed results. Large scale effectiveness trials (under public health intervention conditions/programmatic conditions) have not been undertaken. In 1980s, another formula for production of DFS, using the encapsulation process for fortification of salt with iron and iodine, was developed by Micronutrient initiative (MI) - referred to as Micronutrient Initiative (MI) formula or MI-DFS. Both DFS-NIN and DFS-MI formulae are being used by Tamil Nadu State Government for ICDS and Mid-Day Meal Programme in the state. In 1990s, Sunder Chemicals also produced DFS using its own formula and undertook efficacy trials. The Human Nutrition Laboratory, Swiss Federal Institute of Technology, Switzerland also has a DFS formula, which has not been used or tried in India. However, findings from efficacy trials of this DFS are available in the peer review scientific journals. To date, only one multi-micronutrient fortified edible salt (MMNS) has been produced in India. This was produced by Sundar Chemicals Pvt Ltd., a private sector undertaking, in 1990s.Edible Salt is fortified with 10 micronutrients, namely, Iron, Iodine, vitamin A, vitamins B1, B2, B6, B12, Folic Acid, Niacin and Calcium. The results of the efficacy trials have been published in peer reviewed scientific journals. A positive impact has been documented on the micronutrient status of the beneficiaries consuming such fortified salt. The Ministry of Women and Child Development has adopted a policy that NIN-DFS is to be utilized for the feeding component of the ICDS programme. There are more than 10 salt producers who have been recognized by NIN as producers of double fortified salt using NIN-DFS formula and are supplying DFS to ICDS in selected states. In Tamil Nadu state, the mid- day meal programme in schools also use DFS, produced by Tamil Nadu Salt Corporation, using NIN or MI formulae.